Occurrence and Diversity of CTX-M-Producing Escherichia coli From the Seine River - Girlich, Delphine; Bonnin, Rémy A.; Naas, Thierry (Frontiers in Microbiology, 2020)
CTX-M-producing Escherichia coli are spreading since 1999 both in clinical and in community settings. Environmental samples such as rivers have also been pointed out as being vectors for ESBL producers. In this report, we have investigated the presence and the diversity of CTX-M-producing E. coli isolates in two samplings of the Seine River (next to Notre Dame), Paris France, performed in June 2016 and 2017. The total number of bacteria growing on the selective ChromID ESBL agar was 3.1 × 105 cfu/L (23.8% of all growing bacteria) in 2016, whereas it was 100-fold lower in 2017 (3 × 103 cfu/L; 8.3% of all growing bacteria). However, among them, the prevalence of ESBL-producing E. coli increased from <0.1 to 1.1% in one-year. ESBLs were exclusively of the CTX-M-type: CTX-M-1 (n = 5), CTX-M-15 (n = 7), CTX-M-14 (n = 1), and CTX-M-27 (n = 2). The isolates belonged to several multi locus sequence types, and a wide diversity of incompatibility groups of plasmids were identified in those E. coli isolates. The occurrence and diversity of E. coli isolates belonging to many clones and producing many CTX-M-variants have been identified in our study. The presence of these bacteria in rivers that are open again for recreational usage (swimming) is worrying as it may contribute to further dissemination of ESBL producers in the community.